How Digital and Oral Peer Feedback Improves High School Students' Written Argumentation-A Case Study Exploring the Effectiveness of Peer Feedback in Geography - Michael Morawski; Alexandra Budke (MDPI AG, 2019)
This article approaches written argumentation as a concept of promoting geographical literacy. It is argued that student-centered peer feedback is an effective method with which to improve individual students’ argumentative texts. This research uses a case-study design, which analyzed how high school students in different pairs improve their argumentation text under subject-specific criteria. For the feedback process, a subject-specific feedback sheet for students has been designed for them to review their partner’s argumentative text. The findings mainly suggest two outcomes: Different kinds of feedback in terms of interaction, content and argumentative integration of text material lead to text improvement, and that there are varying complexities of feedback acceptance in terms of subject-specific criteria. The results provide a deeper insight into how students can be prepared and rewarded for producing qualitatively high and effective feedback on argumentative texts in socio-scientific contexts with a strong focus on the (linguistic) skills they need for these procedures.